2023
DOI: 10.1007/s00425-023-04279-w
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular nitric oxide sustains root surface redox activity and growth under sudden flooding-induced hypoxic conditions in barley root tips

Veronika Zelinová,
Loriana Demecsová,
Ľubica Liptáková
et al.

Abstract: Main conclusion Nitric oxide sustains root tip surface redox activity and restricts lipid peroxidation-triggered cell death in the root tips. Abstract In order to gain more insight into the involvement of nitric oxide (NO) in plant response to sudden flooding-induced hypoxic stress, we studied the effect of two NO donors, sodium nitroprusside and S-nitroso-L-glutathione, on short-term partial submergence-induced root growth inhibition, alteration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…It has been reported that NO application applied under ooding situations in corn makes a signi cant contribution by reducing membrane damage (Jaiswal and Srivastava, 2015). Similarly, it has been reported that NO applications in barley regulate cellular events by contributing to plasma membrane electron transport (Zelinová et al, 2024). In our study, it was revealed that RWC and MD were negatively affected by ooding stress and that the applied NO doses made a signi cant contribution to the regulation of cellular events.…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that NO application applied under ooding situations in corn makes a signi cant contribution by reducing membrane damage (Jaiswal and Srivastava, 2015). Similarly, it has been reported that NO applications in barley regulate cellular events by contributing to plasma membrane electron transport (Zelinová et al, 2024). In our study, it was revealed that RWC and MD were negatively affected by ooding stress and that the applied NO doses made a signi cant contribution to the regulation of cellular events.…”
Section: Discussionsupporting
confidence: 71%